New page design : layout & editorial design - Wang, Shaoqiang (Barcelona, Spain : Hoaki Books, S.L., 2022)
"Now in paperback, New Page Design offers a comprehensive technical explanation of basic layout principles, a crucial graphic design field that covers the arrangement of typefaces, images, colours, objects, and grids on a page. New Page Design presents also a panorama of contemporary editorial design trends and styles through a selection of 100 projects, from newspapers and magazines to catalogues, books, brochures and posters. Supported by case studies and tips and tricks, within this book readers will gain an overall understanding of the fundamentals of editorial design, including paper size, typographic units, the history of typography and the styles of different typefaces, layout elements, interaction between sections, and the optimum way to visually convey a message. It is a perfect reference for designers who are looking for practical solutions and inspiration. The book includes interviews with Bruch --Idee & Form, Any Studio, Pyramid and Linus Lohoff"--
PREFACE / by Jose Moreno at creanet -- FUNDAMENTALS OF PAGE DESIGN. Paper size standards ; Typographic measurement ; Typography ; Page layout and grid system -- MAGAZINE. Dolomitenstadt Magazine ; Interview with Bruch--Idee & Form ; 47° ; Fluchtpunkt Stadt ; Interview with Any Studio ; Land in Sicht! ; Redesign of Cartelera Turia ; Slanted Magazine #31: Tokyo ; BAU ; Kaleidoscope Asia issue no. 3 ; Papel Vivo ; 12 Architecture Magazine ; Space Explorer ; 02point2 #6 ; Format Wars ; The Blueprint Magazine ; I love Chatsworth Road ; Crop Magazine ; Redesign of Sort Mælk ; komma 21 ; Amalgam Journal ; Handbook to Extraordinary Culture ; Audi Magazine SS18 ; The Shining: Screenplay ; Magma ; komma 18 ; F!nePrint Magazine ; Food for Thought ; Welcome to Sweden -- BOOK. London type ; Interview with Pyramid ; Biomimesis ; First: The humans in space ; Ladurée: El placer del Macaron ; Da Vinci: Ladies portraits ; New Vienna now ; The confessions ; IBM, Paul Rand's graphic standards manual reprint ; The Chelsea Hotel ; No encalço dos bufões ; Kape 24 h cookbook ; Physics for USSR -- POSTER. Experimental Film Society poster series ; Interview with Pouya Ahmadi ; It is what it is ; Interview with Linus Lohoff ; 384.400 km ; Next Wave Festival 2018: posters ; Constantin Brâncuși ; Tuder Ballet studio ; BR Orchestra season 18-19 ; Typographic poster series ; Self-publishing for Almanacco di Quartiere ; NOW ; Typographic theatre posters -- OTHER FORMAT. Next Wave Festival 2018: Programme ; Interview with M. Giesser ; Arts House: Season 1 in 2018 ; BWA Wroclaw winter brochure ; Paracelsus annual report ; Salzburg global president's report 2017 ; Occupy Earth exhibition booklet ; Design code ; Reyko ; New Order catalogue ; Mane Tatoulian Branding ; Hier und Hier ; The Journal issue 4. by B&O PLAY ; SPIL ; TIFF annual report ; Consecotaleophobia ; Panama Plus Festival ; Energy Natural Systems ; Provisional figures ; CSR report 2017 ; Melt! Music Journal
"Magazine, book, poster, brochure, catalogue, annual report, newspaper"--Cover
Designers include: Alsu Gilmanova ; Amanda & Erik ; Andrés Higueros ; Any Studio ; Blok Design ; Bond Creative Agency ; Brando Corradini ; Brian Liu ; Bruch--Idee & Form ; Bureau Borsche ; Candice Alencar, Nayelli Jaraba ; Carina Mähler ; Carla Cabras ; Clara.B Landín ; creanet ; Cristóbal Riesco ; David Reca ; Dominik Langegger ; Due Collective ; Ekaterina Nikolaeva ; Empire, Syndicat ; Estúdio Lampejo ; Fatih Hardal ; Format Wars ; Galya Dautova, Karina Yazylyan ; GeneralPublic ; Gusto IDS ; Karolina Pietrzyk, Mateusz Zieleniewski ; komma team ; Leticia Ortín ; Line Marie Rasmussen ; Linus Lohoff ; Lucas Depolo Machado ; M. Giesser ; Mane Tatoulian ; Miriam König ; Moby Digg ; Muttnik ; My Name is Wendy ; Pouya Ahmadi ; Pyramid ; Rasmus Jappe Kristiansen ; Sagmeister & Walsh ; Slanted Publishers ; Sofia Felgueiras ; Studio Ahremark ; Studio Fréro ; Tania Hoffrén ; Timur Babaev ; Vincenzo Marchese Ragona
Includes index
1
Keywords: Dummies (Bookselling); Graphic arts; Graphic design (Typography); Grids (Typographic design); Layout (Printing); Type and type-founding; Dummies (Bookselling); Graphic arts; Graphic design (Typography); Grids (Typographic design); Layout (Printing); Type and type-founding.